National Cultural Diversity Based on Interactive Multimedia: Elementary School Teachers' and Students' Responses to the Implementation of the Curriculum Merdeka - Gunardi, Ari; Hidayat, Sholeh; Ruhiyat, Yayat (JETL (Journal of Education, Teaching and Learning), 2024)
Learning media plays an important role in improving students' learning abilities. One measure of student success is the application of interactive media implemented by teachers. The purpose of this study was to describe the responses of teachers and fourth grade elementary school students to the use of social studies learning media on the material "Recognizing National Cultural Diversity" in the Curriculum Merdeka based on interactive multimedia. The subjects of this study were 10 social studies teachers and 50 fourth grade students of Al-Azhar Elementary School and Al Munawwaroh Islamic Elementary School, Serang City, Banten, Indonesia. The method used was quantitative descriptive using a questionnaire instrument that measured teacher responses and student responses. The results showed that teachers and students gave a positive response to the use of Social Studies Learning Media on the subject matter "Recognizing National Cultural Diversity" based on interactive multimedia. With the percentage of teacher responses showing 85% with a practical category, then the average student response also showed a practical category with 84.8%. The findings of this study conclude that the use of the Social Studies Learning Media "Recognizing National Cultural Diversity" based on interactive multimedia is already practical in the implementation of the Curriculum Merdeka. Thus, the findings of this study provide challenges and policies on teaching practices related to the Social Studies Learning Media "Recognizing National Cultural Diversity" based on interactive multimedia used in learning in grade IV of elementary school in the Curriculum Merdeka.